Medical malpractice in hospitals—how healthcare staff feel - Tsai, Shang-Feng; Wu, Chieh-Liang; Ho, Yu-Ying; Lin, Pei-Yi; Yao, Ai-Chu; Yah, Ya-Hui; Hsiao, Chia-Min; You, Yu Huei; Yeh, Te-Feng; Chen, Cheng-Hsu (Frontiers in Public Health, 2023)
Literature is limited on quantified acute stress reaction, impact of event scale of medical staff when facing medical malpractice (MMP), and how to individually care for staff. We analyzed data in the Taichung Veterans General Hospital from October of 2015 to December of 2017, including Stanford Acute Stress Reaction Questionnaire (SASRQ), Impact of Event Scale-Revised (IES-R) and medical malpractice stress syndrome (MMSS). Of all 98 participants, most (78.8%) were females. Most MMP (74.5%) did not involve injury of patients, and most staff (85.7%) indicated receiving help from the hospital. Internal-consistency evaluations of 3 questionnaires showed good validity and reliability. The highest score of IES-R was the construct of intrusion (30.1), the most severe construct of SASRQ was “Marked symptoms of anxiety or increased arousal”, and the most were having mental and mild physical symptoms for MMES. Higher total IES-R was associated with younger age (<40 y/o), and more severe injury on patients (mortality). Those who indicated receiving very much help from the hospital were those having significantly lower SASRQ sores. Our study highlighted that hospital authority should regularly follow-up staffs’ response to MMP. With timely interventions, vicious cycles of bad feelings can be avoided, especially in young, non-doctor, non-administrative staff.